Dividend Policy And Consumer Goods Sector In Nigeria - CHIJUKA, IFY MICHAEL; Hussein, Momoh (EuroEconomica, 2023)
This study examines the influence of consumer goods internal determinants on dividend policy in Nigerian from 2017 to 2021. This study uses a panel data regression model with pairwise testing for data analysis. Purposive sampling was employed in data collection. The internal determinants that influence dividend policy included in this study are: ratio of current asset, ratio of debt-to-equity, assets growth and collateralizable assets, as well as return on equity while the dependent variable is ratio of Dividend Payout. The findings of this research revealed that the ratio of dividend payout is unaffected by the current ratio, the debt-to-equity ratio, or growth. Dividend policy is influenced positively by Collaterization and Return on Equity. Consumer goods companies, according to this study, are more likely to pay out significant dividends to shareholders if they are profitable and have a large pool of collateral with which to back their claims. Studies show that managers are allowed to increase dividends to shareholders, which supports agency theory. According to study findings both theoretical and empirical, in the Nigerian consumer goods industry, where profits are high and collateral is available, companies prefer to give significant dividends to shareholders.